Evaluation of Non-Vector Transmission of Usutu Virus in Domestic Canaries (Serinus canaria) - Aude Blanquer; Felipe Rivas; Mazarine Gérardy; Michaël Sarlet; Nassim Moula; Ute Ziegler; Martin H. Groschup; Daniel Desmecht; Thomas Marichal; Mutien Garigliany (Viruses, 2024)
Usutu virus (USUV) is a flavivirus transmitted to avian species through mosquito bites that causes mass mortalities in wild and captive bird populations. However, several cases of positive dead birds have been recorded during the winter, a vector-free period. To explain how USUV “overwinters”, the main hypothesis is bird-to-bird transmission, as shown for the closely related West Nile virus. To address this question, we experimentally challenged canaries with intranasal inoculation of USUV, which led to systemic dissemination of the virus, provided the inoculated dose was sufficient (>102 TCID50). We also highlighted the oronasal excretion of infectious viral particles in infected birds. Next, we co-housed infected birds with naive sentinels, to determine whether onward transmission could be reproduced experimentally. We failed to detect such transmission but demonstrated horizontal transmission by transferring sputum from an infected to a naive canary. In addition, we evaluated the cellular tropism of respiratory mucosa to USUV in vitro using a canary tracheal explant and observed only limited evidence of viral replication. Further research is then needed to assess if and how comparable bird-to-bird transmission occurs in the wild.